Integrating gender perspectives to prevent or reduce climate crisis impacts - Alvi, Muzna; Ringler, Claudia; Bryan, Elizabeth (Welternährung, 2023)
We cannot overcome the multiple crises facing our world, including the climate crisis, the lingering impacts of the COVID-19 pandemic, and the ongoing food and energy price crisis linked to the war on Ukraine, without integrating a gender perspective into resilience interventions, particularly in the agri-food sector where women have particular roles. However, to date, most climate change policies, investments, and interventions remain gender-blind. As a result, they might exacerbate gender inequalities in food systems by, for instance, increasing women’s labor burden and time poverty, reducing their access to and control over income and assets, and reducing their decision-making power.